Effect of group cognitive behavioral therapy and group interpersonal psychotherapy on aggression among first grade university students in China - Li, Yutong (2017)
Aggression is best described as any form of action pointed to the target of hurting or damaging another living being who intends to avoid such action. In recent years, a series of vicious incidents occurred in campuses of mainland China and caused irreparable loss for school, family and society. However, intervention studies among Chinese university students are very few at present. At the same time, there is imbalance between theory study and practice of aggression intervention. In this sense, further studies on aggression intervention are more important. The objectives of this study mainly include determining the effect of group cognitive behavioral therapy (G-CBT) and group interpersonal psychotherapy (G-IPT) for aggression and comparing the intervention effect of G-CBT and G-IPT for aggression among the first grade university students of China. This research is a randomized, pre- posttest with control group design. Through stratified random sampling, 1,469 first grade students, who were from three Chinese universities and age from 18 to 19 years old were obtained. The participants whose score achieved the evaluation standard of aggression were selected and in a random way, 90 subjects were averagely divided into three schemes— G-CBT, G-IPT and the control group. The subjects of G-CBT and G-IPT received 16 sessions of treatment, while subjects in the control group did not receive any intervention. All subjects completed the assessment for three times: pretest, posttest 1 and posttest 2. The results showed: 1, for G-CBT, the total score and the scores of all subscales of aggression had dropped significantly (p<.05); 2, for G- IPT, the total score and the scores of all subscales of aggression had dropped significantly (p<.01), 3, in the posttest 1, the scores of total aggression, impulsivity and hostility of the G-IPT group were significantly lower than the G-CBT group (p<.01), in the posttest 2, the scores of total aggression and hostility of the G-IPT groups were significantly lower than the G-CBT group (p<.01). Therefore, for Chinese college students, 1, the G-CBT is effective in treating aggression and the effect is stable; 2, the G-IPT is effective in treating aggression and the effect is stable; 3, the G-IPT is better than the G-CBT in reducing aggression and the effect is stable.